"EYE FAMILY": THE URBAN DAILY, THE MORAL WORK AND THE SOCIAL CONTROL IN UBERABA (1945-1964) - Querino, Rosimar Alves (Cadernos CERU, 2003)
Between the 1940s and the 1960s, the city of Uberaba/MG passed through some significant changes in its urban site. In this article, the main concern was to identify the several looks on beggars and poor people and the intervention proposals and services to this part of population. Tha main sources of this study - the Municipal Posture Code and the local newspaper Lavoura e Comércio - were analysed from a bibliographic review round the positive value of work, the moral of the poor and the social control as founding elements of the capitalist urban site. The analysis was organised in three parts. In the first one, the positive value of work and the capitalist society constitution were recovered. In the second part, even though it was fair briefly, the importance of work on the Brazilian social issue discussion was pointed out. And at last, some faces of the social issue in  Uberaba were studied again with special concern to the poverty representation and the types of interventions proposed.